(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2020)
The Bali Aga community in northern Bali and the Ainu in northern Japan are indigenous peoples who share in utilising a wealth of folktales as a vehicle for passing down their respective local wisdom across generations. This study comparatively examines Bali Aga and Ainu discourses of local wisdom expressed implicitly and explicitly in these folktales. The focus of the study is to analyse discourses of local wisdom, in particular those relating to nature conservation as reflected in the folktales. The research data were taken from selected Bali Aga and Ainu folktales and analysed through the theoretical lenses of literary anthropology and comparative literature. The analysis shows that in addition to having an aesthetic narrative structure, the Bali Aga and Ainu folktales are also rich in depictions of life skills knowledge, farming methods, livelihoods and cultural values that are useful for fostering public awareness in conserving nature as a resource for cultural maintenance. This article concludes that the folktales of these two ethnic groups offer local wisdom useful for fostering awareness in society of the importance of conserving nature, with the message that despite its abundant resources, nature should not be exploited.